If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + -1) = 2(4x + -7) Reorder the terms: 3(-1 + 2x) = 2(4x + -7) (-1 * 3 + 2x * 3) = 2(4x + -7) (-3 + 6x) = 2(4x + -7) Reorder the terms: -3 + 6x = 2(-7 + 4x) -3 + 6x = (-7 * 2 + 4x * 2) -3 + 6x = (-14 + 8x) Solving -3 + 6x = -14 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -3 + 6x + -8x = -14 + 8x + -8x Combine like terms: 6x + -8x = -2x -3 + -2x = -14 + 8x + -8x Combine like terms: 8x + -8x = 0 -3 + -2x = -14 + 0 -3 + -2x = -14 Add '3' to each side of the equation. -3 + 3 + -2x = -14 + 3 Combine like terms: -3 + 3 = 0 0 + -2x = -14 + 3 -2x = -14 + 3 Combine like terms: -14 + 3 = -11 -2x = -11 Divide each side by '-2'. x = 5.5 Simplifying x = 5.5
| 0.3x+33.6=51 | | 7x-10=x+2 | | 7.3x-5.8+2.5x= | | F(x)=2x^2+5x+9 | | 56=24(1/6z+5/6) | | 8x=27-x | | H=-16t^2+72t+3 | | -38.5=4.3z-4.1 | | 2x+4-3x=9 | | 24-2x=-6x+4 | | 2x+6-5x=-3 | | 3.1=1.3+2.9 | | 16=20(1/5z+4/5) | | H=-16t+72t+3 | | 5x+2-3x=-2 | | (X+4)(5x-1)=0 | | 3x+6-4x=8 | | a^2=135+6a | | 3x+4-2x=9 | | 38x-13=5(7x-1)+3x-8 | | -6x=-4x-16 | | (x+3)(x+6)+(x+3)(x+6)= | | 3x-5-6x=4 | | 7(z+3)-5z=9 | | 5(5-y)/3=y | | Y^2/30=y/15+1/2 | | 5x-8-6x=-7 | | -5(4x-7)+3=-20x+38 | | 34-3x=6x-2 | | 4n+7=6n+1 | | 3x+4-6x=7 | | 10p^2+60p=50 |